Estudio de factibilidad para la construcción de una residencia universitaria en el Barrio Zumbalica del Cantón Latacunga - Guanoluisa Arequipa, Luis Hernán (2021)
This entrepreneurship proposal is born from the experience and direct observation of the houses that offer accommodation to the students of the Technical University of Cotopaxi, for which the construction of a building that provides the University Residence service in the Zumbalica neighborhood is proposed, with the provision of additional and personalized services. This entrepreneurship proposal is supported by a feasibility study that will allow minimizing the risk at the time of the start-up of the project; Through an online survey applied to foreign students, and thanks to direct observation and an interview, the offer of this service was determined, and finally, thanks to the technical study, the capacity to be installed and the total amount of the investment were determined. For the execution of the project, USD 74,562.72 of own capital is available, USD 90,000.00 will be financed, giving a total of USD 164,562.72 necessary for the investment in the 5-storey building for the Residence, with a total of 20 nini departments that will house 28 students. Once the study is completed, a VA of $ 187,490.35 is obtained, a VAN of $ 22,927.63 and a TIR of 10.30%, concluding that the project is viable.